Higher gastric parietal cell antibody titer significantly increases the frequencies of macrocytosis, serum vitamin B12 deficiency, and hyperhomocysteinemia in patients with burning mouth syndrome - Ying-Tai Jin; Yu-Hsueh Wu; Yang-Che Wu; Julia Yu-Fong Chang; Chun-Pin Chiang; Andy Sun (Elsevier, 2022)
Background/purpose: Our previous study found 109 gastric parietal cell antibody (GPCA)-positive burning mouth syndrome (BMS) patients (so-called GPCA+BMS patients in this study) in a group of 884 BMS patients. This study evaluated whether high-titer (GPCA titer ≥ 160) GPCA+BMS patients had greater frequencies of macrocytosis, anemia, serum iron and vitamin B12 deficiencies, and hyperhomocysteinemia than low-titer (GPCA titer < 160) GPCA+BMS patients or 442 healthy control subjects. Materials and methods: Complete blood count, serum iron, vitamin B12, folic acid, homocysteine, and GPCA levels in 42 high-titer GPCA+BMS patients, 67 low-titer GPCA+BMS patients, and 442 healthy control subjects were measured and compared. Results: We found that 33.3%, 38.1%, 19.0%, 33.3%, 2.4%, and 57.1% of 42 high-titer GPCA+BMS patients and 10.4%, 25.4%, 14.9%, 6.0%, 1.5%, and 11.9% of 67 low-titer GPCA+BMS patients were diagnosed as having macrocytosis, blood hemoglobin, iron, vitamin B12, and folic acid deficiencies, and hyperhomocysteinemia, respectively. Moreover, both 42 high-titer and 67 low-titer GPCA+BMS patients had significantly greater frequencies of macrocytosis, blood hemoglobin, serum iron and vitamin B12 deficiencies, and hyperhomocysteinemia than 442 healthy control subjects (all P-values < 0.001). In addition, 42 high-titer GPCA+BMS patients also had greater frequencies of macrocytosis, serum vitamin B12 deficiency, and hyperhomocysteinemia than 67 low-titer GPCA+BMS patients (all P-values < 0.01). Conclusion: The high-titer GPCA+BMS patients have significantly greater frequencies of macrocytosis, anemia, serum iron and vitamin B12 deficiencies, and hyperhomocysteinemia than healthy control subjects and significantly greater frequencies of macrocytosis, serum vitamin B12 deficiency, and hyperhomocysteinemia than low-titer GPCA+BMS patients.